Goals and games designing your employee's goals like game designers design video games - Edery, David 1976- (FTPress Delivers, 2010)
"This Element is an excerpt from Changing the game: how video games are transforming the future of business (ISBN: 9780132357814) by David Edery and Ethan Mollick. Apply the lessons of game design to supercharge employee productivity, performance, creativity, and satisfaction!"--Resource description page.
Includes bibliographical references. - Online resource; title from PDF title page (EBSCO, viewed January 23, 2018)
Keywords: Goal setting in personnel management; Employees -- Training of; Video games -- Design; Personnel; Direction; Fixation des objectifs; Personnel; Formation; Jeux vidéo; Conception; BUSINESS & ECONOMICS / Industrial Management; BUSINESS & ECONOMICS / Management; BUSINESS & ECONOMICS / Management Science; BUSINESS & ECONOMICS / Organizational Behavior; Employees; Training of; Video games; Design